Water dynamics affects thermal transport at the surface of hydrophobic and hydrophilic irradiated nanoparticles. Issue 8 (1st May 2020) - Salassi, Sebastian; Cardellini, Annalisa; Asinari, Pietro; Ferrando, Riccardo; Rossi, Giulia
Abstract : Plasmonic nanoparticles, such as Au nanoparticles (NPs) coated with bio-compatible ligands, are largely studied and tested in nanomedicine for photothermal therapies. Abstract : Plasmonic nanoparticles, such as Au nanoparticles (NPs) coated with bio-compatible ligands, are largely studied and tested in nanomedicine for photothermal therapies. Nevertheless, no clear physical interpretation is currently available to explain thermal transport at the nanoparticle surface, where a solid–liquid (core–ligand) interface is coupled to a liquid–liquid (ligand–solvent) interface. This lack of understanding makes it difficult to control the temperature increase imposed by the irradiated NPs to the surrounding biological environment, and it has so far hindered the rational design of the NP surface chemistry. Here, atomistic molecular dynamics simulations are used to show that thermal transport at the nanoparticle surface depends dramatically on solvent diffusivity at the ligand–solvent interface. Furthermore, using physical indicators of water confinement around hydrophobic and hydrophilic ligands, a predictive model is developed to allow the engineering of NP coatings with the desired thermal conductivities at the nanoscale.